Microdialysis Determination of Cefquinome Pharmacokinetics in Murine Thigh From Healthy, Neutropenic, and Actinobacillus pleuropneumoniae-Infected Mice - Zhang, Longfei; Yao, Lihua; Kang, Zheng; Huang, Zilong; Gu, Xiaoyan; Shen, Xiangguang; Ding, Huanzhong (Frontiers in Pharmacology, 2019)
This study was aimed at applying microdialysis to explore cefquinome pharmacokinetics in thigh and plasma of healthy, neutropenic, and Actinobacillus pleuropneumoniae-infected mice. The relative recoveries (RRs) were tested in vitro by dialysis and retrodialysis and in vivo by retrodialysis. ICR mice were randomly divided into four groups: H-40 mg/kg (healthy mice receiving cefquinome at 40 mg/kg), H-160 mg/kg, N-40 mg/kg (neutropenic mice), and I-40 mg/kg (thigh infected-mice with A. pleuropneumoniae). After cefquinome administration, plasma was collected by retro-orbital puncture and thigh dialysate was collected by using a microdialysis probe with Ringer's solution at a perfusion rate of 1.5 L/min. Plasma and thigh dialysate samples were assessed by HPLC-MS/MS and analysed by a non-compartment model. The mean in vivo recoveries in the thigh were 39.35%, 38.59%, and 37.29% for healthy, neutropenic, and infected mice, respectively. The mean plasma protein binding level was 16.40% and was independent of drug concentrations. For all groups, the mean values of the free AUCinf in plasma were higher than those in murine thigh, while the elimination T1/2β for plasma were lower than those for murine thigh. Cefquinome penetration (AUCthigh/AUCplasma) from the plasma to thigh was 0.70, 0.81, 0.49, and 0.98 for H-40, N-40, I-40, and H-160 mg/kg, respectively. These results indicated that infection significantly affected cefquinome pharmacokinetics in murine thigh. In conclusion, we successfully applied a microdialysis methods to evaluate the pharmacokinetics of cefquinome in murine thigh of healthy, neutropenic, and A. pleuropneumonia-infected mice and the pharmacokinetics of cefquinome was obviously affected by infection in thigh.